Future Direction of IMIA Standardization - Nakaya, J.; Kimura, M.; Ogishima, S.; Shabo, A.; Kim, I. K.; Parisot, C.; de Faria Leao, B. (Yearbook of Medical Informatics, 2014)
Objectives: Standardization in the field of health informatics has increased its importance and global alliance for establishing interoperability and compatibility internationally. Standardization has been organized by standard development organizations (SDOs) such as ISO (International Organization for Standardization), CEN (European Committee for Standardization), IHE (Integrating the Healthcare Enterprise), and HL7 (Health Level 7), etc. This paper reports the status of these SDOs’ activities.Methods: In this workshop, we reviewed the past activities and the current situation of standardization in health care informatics with the standard development organizations such as ISO, CEN, IHE, and HL7. Then we discussed the future direction of standardization in health informatics toward “future medicine” based on standardized technologies.Results: We could share the status of each SDO through exchange of opinions in the workshop. Some WHO members joined our discussion to support this constructive activity.Conclusion: At this meeting, the workshop speakers have been appointed as new members of the IMIA working groups of Standards in Health Care Informatics (WG16). We could reach to the conclusion that we collaborate for the international standardization in health informatics toward “future medicine”.
Keywords: Standardization; ISO; health; HL7; WHO